2020
DOI: 10.1089/hum.2020.167
|View full text |Cite|
|
Sign up to set email alerts
|

Adeno-Associated Virus-Induced Dorsal Root Ganglion Pathology

Abstract: The administration of adeno-associated virus (AAV) vectors to nonhuman primates (NHP) via the blood or cerebrospinal fluid (CSF) can lead to dorsal root ganglion (DRG) pathology. The pathology is minimal to moderate in most cases; clinically silent in affected animals; and characterized by mononuclear cell infiltrates, neuronal degeneration, and secondary axonopathy of central and peripheral axons on histopathological analysis. We aggregated data from 33 nonclinical studies in 256 NHP and performed a meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(188 citation statements)
references
References 10 publications
9
161
1
2
Order By: Relevance
“…We found no sign of cellular degeneration that is commonly observed when the AAV vector is administrated via blood or cerebrospinal fluid. 40 Therefore, we concluded that the AAV vectors applied via the intra-nerve route at the current titer (1.2 × 10 12 gc/6 μL/animal) did not have their own toxic effects on DRG neurons.
Figure 3 H&E-stained DRG sections Hematoxylin and eosin (H&E)-stained DRG sections stained 4 weeks after the sciatic nerve injections of AAV9-GFP (A–C), AAV6-GFP (D–F) vectors, and control (G and H) in the marmoset (A, B, D, E, and G) or rat (C, F, and H).
…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…We found no sign of cellular degeneration that is commonly observed when the AAV vector is administrated via blood or cerebrospinal fluid. 40 Therefore, we concluded that the AAV vectors applied via the intra-nerve route at the current titer (1.2 × 10 12 gc/6 μL/animal) did not have their own toxic effects on DRG neurons.
Figure 3 H&E-stained DRG sections Hematoxylin and eosin (H&E)-stained DRG sections stained 4 weeks after the sciatic nerve injections of AAV9-GFP (A–C), AAV6-GFP (D–F) vectors, and control (G and H) in the marmoset (A, B, D, E, and G) or rat (C, F, and H).
…”
Section: Resultsmentioning
confidence: 72%
“…To confirm whether these observations might be influenced by potential immune cell infiltration, 33 , 39 , 40 we examined the immune responses of DRG cells by histological examination of hematoxylin and eosin (H&E)-stained DRG sections in both the rat and marmoset ( Figure 3 ).We found little sign of cellular infiltration in the AAV-9 injected (A–C), the AAV-6 injected (D–F), and the control animals (G and H). We found satellite cells or lymphocytes in every section, but they were not at the level of differentiating into macrophages, and we found no significant difference between the AAV-injected and control DRGs.…”
Section: Resultsmentioning
confidence: 96%
“…The microscopic findings in the DRG, spinal cord, and peripheral nerve were associated with proprioceptive deficiencies in piglets, but in NHP, CNS clinical signs are very rarely observed. Using aggregate data from 33 monkey studies that evaluated five different capsids, five different promoters, and 20 different transgenes, Hordeaux et al (2020a) were able to demonstrate that following rAAVbased gene therapies, DRG toxicity occurred more frequently when given via the cerebral spinal fluid (vs IV route), and severity increased with IV dose, and was more severe when administered to adult (vs juvenile) animals.…”
Section: Toxicity To Dorsal Root Gangliamentioning
confidence: 99%
“…Therefore, to perform and deeply analyze immunotoxicity studies is essential to succeed in gene therapy studies. For instance, toxicity has been recently reported in the dorsal root ganglion (DRG) sensory neurons [69] after AAV injection in non-human primates. According to this study, DRG pathology was more severe when higher dose vector or older animals were injected.…”
Section: In Vivo Gene Therapy and Aav Vectorsmentioning
confidence: 99%